PENERAPAN STRATEG PRACTICE REHEARSAL PAIRS DALAM PENINGKATAN PEMBELAJARAN IPA TENTANG CAHAYA KELAS V SDN KALIJARAN 01 TAHUN AJARAN 2012/2013 - sujiyanto, rahmat (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Implementation of Practice Rehearsal Pairs Strategy In Improving Natural Sciences 5th Grade in Kalijaran 01 Maos Cilacap. The purpose of this research is to describe the step of applaying Practice Rehearsal Pairs strategy in improving natural sciences. This research uses classroom actions research methods with three cycles. Each cycle consist of two meeting, each meeting consist planning, action, observation, and reflection. Data collecting methods are collected through observation, interview, test and documentation. The validity of data using the triangulation source. The data analysis is used by this research is quantitatif and qualitatif data analysis. The result of research showed that the step of applaying Practice Rehearsal Pairs strategy can improve the natural sciences. The applying improve the study process posed at with the make up of assessment process from 42,36% at cycle I become 85,42% at cycle III and result learn improve equal to 72,91% from result pretes 16,67%. Keywords: Practice Rehearsal Pairs strategy, Improve Learning, Natural Sciences     Abstrak: Penerapan Strategi Practice Rehearsal Pairs dalam Peningkatan Pembelajaran IPA  Kelas V SDN Kalijaran 01 Maos Cilacap. Tujuan penelitian ini adalah mendeskripsikan langkah penerapan strategi Practice Rehearsal Pairs dalam peningkatan pembelajaran IPA. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari dua pertemuan dengan tahap perencanaan, pelaksanaan, observasi, dan refleksi. Teknik pengumpulan data menggunakan observasi, wawancara, tes dan dokumentasi. Validasi data menggunakan teknik triangulasi sumber. Analisis data yang digunakan dalam penelitian ini adalah analisis data kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa langkah penerapan strategi Practice Rehearsal Pairs dapat meningkatkan pembelajaran IPA. Penilaian proses meningkat dari 42,36% pada siklus I menjadi 85,42% pada siklus III, sedangkan hasil belajar meningkat sebesar 72,91% dari hasil pratindakan 16,67%.   Kata kunci: Strategi Practice Rehearsal Pairs, Peningkatan pembelajaran, IPA